Linguistic Means of Expression Imagery in Khrystya Alchevska's Poetry - Черемська, О. С.; Масло, О. В. (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2017)
The article investigates main features of Khrystya Alchevska’s poetry, in particular, the deepening individual style of the poet in the verbal symbolism and folk-song art. The analysis of verbal and figurative resources of the writer’s poetic language has been made, including symbolic images, coloring, epithets, similes, metaphorical combinations, verbal images, appositions; we have also focused on the methods of personification and aestheticization, use of parallelism, palillogy, anaphora.